Clinical Syndrome of Seizures, Headache, and Visual Blurring in Metastatic Carcinoma Colon - Raj, Lakshmi; Anoop, T.M.; CA, Rakesh (Indian Journal of Medical and Paediatric Oncology, 2023)
A 51-year-old lady diagnosed as a case of metastatic carcinoma colon stage IV involving lung and left adrenal metastasis was initiated with palliative chemotherapy with FOLFOX-6 chemotherapy infusion regimen that consisted of 5-flurouracil, calcium leucovorin, and oxaliplatin and injection bevacizumab was added to cycle seven of FOLFOX-6 chemotherapy. After 2 months of initiating bevacizumab, she was presented with one episode of generalized tonic clonic seizure, headache, and visual blurring of 2 days duration and magnetic resonance imaging brain T2 fluid-attenuated inversion recovery image revealed subcortical white matter edema in bilateral frontoparietal, occipital, left temporal lobes (Fig. 1A and B), and hyperintense edema with effacement of folia in both cerebellum with nodular areas of contrast enhancement suggestive of posterior reversible encephalopathy syndrome.
Keywords: bevacizumab; medical oncology; posterior reversible encephalopathy syndrome (PRES); magnetic resonance imaging